Ре­ши­те урав­не­ние: 3*9^(x-1/2)+7*6^x+3*4^(x+1)=0

0 голосов
7.4k просмотров

Ре­ши­те урав­не­ние: 3*9^(x-1/2)+7*6^x+3*4^(x+1)=0


Алгебра (35 баллов) | 7.4k просмотров
Дан 1 ответ
0 голосов
Правильный ответ

Решите задачу:

3\cdot9^{x-\frac{1}{2}}+7\cdot6^x+3\cdot4^{x+1}=0, \\ 3\cdot(3^2)^{x-\frac{1}{2}}+7\cdot(2\cdot3)^x+3\cdot(2^2)^{x+1}=0, \\ 3\cdot3^{2x-1}+7\cdot2^x\cdot3^x+3\cdot2^{2x+2}=0, \\ 3^{2x}+7\cdot2^x\cdot3^x+12\cdot2^{2x}=0, \\ (\frac{3}{2})^{2x}+7\cdot(\frac{3}{2})^x}+12=0, \\ (\frac{3}{2})^x=t, \ t\ \textgreater \ 0,\\ t^2+7t+12=0, \\ t_1=-4\ \textless \ 0, \ t_2=-3\ \textless \ 0, \\ x\in\varnothing.
(93.5k баллов)